Meningkatkan Kemampuan Motorik Halus Anak Dengan Kegiatan Bermain Plastisin - Nining Hartati; Rizki Amalia; Yolanda Pahrul (Jurnal Pendidikan Tuntas, 2023)
This study aims to improve children's fine motor skills with plasticine play activities, motivated by the low fine motor skills in group B children of Dharma Bakti Kindergarten. The method used in this research is the Classroom Action Research method (PTK). This class action research was carried out in 2 cycles, in each cycle there were 2 meetings. The research subjects were children of Tulip class, group B of Dharma Bakti Kindergarten, totaling 11 children. The object of research is using plasticine media. Data collection techniques used are observation techniques and documentation techniques. The results showed an increase in fine motor skills in each indicator. It can be seen from the results in cycle II action, where in the indicator of working the fingers BB 0 children or 0% MB value 1 child or 9.09% BSB value 2 children or 18.18% BSH value 8 children or 72.73%. There is also an indicator of moving the wrist value BB 0 children or 0% value MB 0 children or 0% BSH 2 or 18.18% value BSB 8 children or 72.73% value. Indicators of eye-hand coordination BB value 0 children or 0% MB value 1 child or 9.09% BSB value 3 children or 27.02% and BSB value 7 children or 63.89% showed that children's fine motor skills had increased in cycle II. Keywords: Fine Motor Skills, Play Activities, Plasticine Media